EJA'S CHALLENGES: : FROM SCHOOL FAILURE TO DROPOUT - Maria Pereira Ribeiro Santos, Janaina; Carlos da Silva, José (Revista Gênero e Interdisciplinaridade, 2021)
The discussion of this text arose due to an elective discipline in the education of young people, adults where we felt the need to meet the challenges of EJA (Youth and Adult Education), from school failure to dropout. Starting to identify what leads to school failure. We tried to verify the current readings of texts and find answers and proposals to contribute to the reduction of this evasion, seeking support in classical theoretical contributions